Young female gamers: Their situation in the use of video games - González-Sancho, Roy (2021)
Research on video games is presented as a current, innovative and constantly developing space. In order to explore video games from a Latin American and gender-based perspective to the discussion, this work focuses on proposing an initial analysis of the situation of young women players who participate in this activity either professionally or casually. This article is based on an exhaustive review of scientific articles and audiovisual productions related to this topic. The results have been divided into four subcategories: exclusion and gender stereotypes; gamer identity; participation of women in e-sports and women competitors in professional and casual teams and reception of the male hegemonic speech. Finally, some reflections and questions are discussed by the researchers, which aim to provide possible study routes in Latin American and local studies of video games.